Novel nanosynthesis of In2O3 and its application as a resistive gas sensor for sevoflurane anesthetic. Issue 3 (14th November 2014) - Karmaoui, M.; Leonardi, S. G.; Tobaldi, D. M.; Donato, N.; Pullar, R. C.; Seabra, M. P.; Labrincha, J. A.; Neri, G.
Abstract : A novel non-aqueous sol–gel route for synthesizing pure In2 O3 nanoparticles using indium acetylacetonate and n -butylamine under solvothermal conditions is herein proposed. Abstract : A novel non-aqueous sol–gel route for synthesizing pure indium oxide (In2 O3 ) nanoparticles (NPs) using indium acetylacetonate and n -butylamine as the reactive solvent, under solvothermal conditions, is herein proposed. The samples were characterized by an advanced X-ray method, whole powder pattern modeling (WPPM) and high-resolution transmission electron microscopy (HR-TEM), showing the exclusive presence of pure In2 O3 . Diffuse reflectance spectroscopy (DRS) was used to determine the optical band gap ( E g ) of the sample. Moreover, these investigations also revealed that the In2 O3 nanoparticles are quasi-spherical in shape, with a diameter of around 7 nm as prepared and 9.5 nm after thermal treatment at 250 °C. In2 O3 NPs worked as highly sensitive sensing interfaces to provide resistance changes during exposure to sevoflurane, a volatile anesthetic agent used in surgical wards. The developed sensor demonstrated a good response and fast response/recovery time towards very low concentrations of sevoflurane in air, suggesting a very attractive application as a real-time monitoring analyzer in a hospital environment.